PEMBERDAYAAN MASYARAKAT MELALUI SOSIALISASI DAN PEMBENTUKAN KELOMPOK TERNAK MADU TRIGONA (TETRAGONULA CLYPEARIS) DI DESA REBAN MADANI LINGSAR - Nursari, Sumita; Suryana, I Gede Putu; Alfianti, Septia (Jurnal Wicara, 2023)
Reban Madani Village is one of the expansion villages in the Batu Mekar area, Lingsar District, West Lombok Regency. Reban Madani Village is a village with a fairly large area of agricultural land, plantations and community forest areas and has several natural tourism sectors so that it has great potential to cultivate trigona honey bees. Trigona honey bee cultivation is one of the creative economy-based community empowerment efforts, which is expected to support and contribute to improving the community's economy in the Batu Mekar village area, especially Reban Madani. This activity aims to develop Trigona honey with business management by initiating the formation of a Trigona honey livestock group with the main step being outreach to the community in Reban Madani Village. With the initial goal of "Community Empowerment Through Socialization and Formation of Trigona Honey Livestock (Tetragonula clypearis) Groups in Reban Madani Lingsar Village" as a supporter of the achievement of Reban Madani Village becoming one of the agro-ecotourism destinations in West Lombok. The target groups for this activity are the local community and the Karang Taruna Group. The results and outputs of the activities after the socialization was carried out, namely that the target community experienced an increase in understanding and skills so that they were able to form Trigona honey cultivation groups. It is hoped that through this activity creative ideas will be generated from the honey cattle groups that have been formed to get good and positive results as initial capital to get new and better livelihoods.